Association between prenatal exposure to maternal metal and trace elements and Streptococcus infection: A prospective birth cohort in the Japan Environment and Children’s Study - Hiroyoshi Iwata; Atsuko Ikeda; Mariko Itoh; Rahel Mesfin Ketema; Naomi Tamura; Takeshi Yamaguchi; Keiko Yamazaki; Rieko Yamamoto; Maki Tojo; Yu Ait Bamai; Yasuaki Saijo; Yoshiya Ito; et al. (PLoS ONE, 2025)
Background Streptococcus infection is a common and potentially severe bacterial infection which remains a global public health challenge, underscoring the necessity of investigating potential risk factors. Aims The present study aims to assess the association between metal and trace element exposure and Streptococcus infection using a prospective nationwide birth cohort, the Japan Environment and Children’s Study (JECS). Methods The JECS obtained data from over 100,000 pregnancies through 15 Regional Centres across Japan. We assessed toxic metal and trace element levels among pregnant mothers and Streptococcus infection among their children, born between 2011 and 2014, at age three to four. Analysis was performed using univariable and multivariable logistic regressions, as well as Quantile g-computation. We also conducted quartile regressions to assess the effects of higher serum selenium levels and potential interactions between selenium and mercury. Results Among 74,434 infants and their mothers, univariable and multivariable regression analyses found that selenium and mercury each had an inverse association with Streptococcus infection incidence. Quantile g-computation analysis yielded results consistent with the primary regression analyses. Quartile regression suggested that serum selenium levels above the third quartile were inversely associated with later Streptococcus infection incidence, but no interaction between selenium and mercury was found. Conclusions These findings imply that maternal selenium exposure may have protective effects on Streptococcus infection among children. Further studies should explore the role of pediatric selenium in immune responses to infectious diseases, especially Streptococcus infection.